Polyphenol-mediated green synthesis of zinc oxide particles and their antibacterial properties: a novel size-controlled approach - Neo, Zhi Zing (2022)
The concept of feasibility in green synthesis of zinc oxide (ZnO) nanoparticles has been discussed thoroughly in many related studies. However, size control using volume of plant extracts undermines potential for process upscaling. This study aimed to improve repeatability and reproducibility of green synthesis of ZnO by controlling total phenolic content of incorporated plant extracts. This study had been conducted by manipulating the molar ratio of zinc nitrate to sodium hydroxide and types of plant extracts. Leaves of Camellia sinensis, Manilkara zapota and Elaeis guineensis had been employed to obtain plant extracts, which were subsequently incorporated at gallic acid equivalent of 100 mgg-1. The phytochemical profile of plant extracts and physical properties of ZnO were determined. In addition, antibacterial activity of dispersed and encapsulated ZnO against Escherichia coli and Staphylococcus aureus was examined. Consistency in particle sizes of ZnO justified the feasibility of using total phenolic content to achieve size control. The roles of phytochemicals were affected by reaction pH. Under neutral pH, the role of phytochemicals as chelating agent predominated. Under basic condition, complex phytochemicals demonstrated structure-directing effect on ZnO microparticles. The antibacterial strength of ZnO reduced by 16 times with the decrement in particle size. Meanwhile, the incorporation of phytochemicals enhanced antibacterial activity of ZnO by fourfold. Encapsulation retained antibacterial strength of ZnO particles with defined microstructures without enhancement. This study confirmed that particle size and morphology of ZnO could be controlled through manipulation of total phenolic content of plant extracts and the reaction pH of green synthesis.